Ekonomi Kreatif : Pelatihan Ekonomi Kreatif untuk Remaja Karang Anyar Praktik Pembuatan Es Susu Gula Aren sebagai Ide Usaha Kekinian - Kasih, I Gede; Anom, Anak Agung Istri; Astraguna, I Wayan (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Creative economy training for Karang Anyar teenagers through the practice of making coconut sugar ice cream is a form of community service. The purpose of this activity is to provide technical skills in making contemporary beverages, foster creativity, and introduce simple marketing strategies that are in accordance with the development of the digital era. The implementation method includes observation, preparation, provision of materials, and direct practice. The results of the training showed an increase in technical skills, creativity, and confidence of adolescents in producing products with economic value. Participants are able to mix ingredients, serve drinks in an attractive way, and understand simple ways to market products through social media. This activity also plays an important role as a positive alternative to reduce adolescent involvement in negative activities such as drunkenness and gambling. Thus, this training not only increases individual capacity, but also opens up new business opportunities that support the sustainable development of the creative economy of village communities.